An indole-based conjugated microporous polymer: a new and stable lithium storage anode with high capacity and long life induced by cation–π interactions and a N-rich aromatic structure. Issue 39 (22nd August 2018) - Wei, Wenxuan; Chang, Guanjun; Xu, Yewei; Yang, Li
Abstract : An indole-based conjugated microporous polymer, poly(bisindolylmaleimide) (PBIM), with superior electrochemical performance as an anode material for LIBs has been obtained by FeCl3 -promoted oxidative coupling polymerization. Abstract : An indole-based conjugated microporous polymer, poly(bisindolylmaleimide) (PBIM), with superior electrochemical performance as an anode material for LIBs has been obtained by FeCl3 -promoted oxidative coupling polymerization. Benefiting from reversible cation–π interactions and a unique aromatic structure containing N heteroatoms, the prepared PBIM anode shows high capacity (1172 mA h g −1, 50 mA g −1 ), outstanding cycle life (1000 cycles), and remarkable rate performance (214 mA h g −1, 2.5C).